Amygdala grey matter volume increase in gambling disorder with depression symptoms of clinical relevance: a voxel-based morphometry study - Zois, Evangelos; Kiefer, Falk; Vollstädt-Klein, Sabine; Mann, Karl (International gambling studies, 2018)
Studies on brain structure in gambling disorder (GD) have so far employed small sample sizes offering little in the investigation of co-morbid conditions such as depression. The aim of the current investigation is to examine grey matter (GM) volume alterations in GD patients with depression symptoms compared to GD without. In total, 107 gamblers with and without depression symptoms were assessed with the Beck Depression Inventory (BDI). The authors employed voxel-based morphometry (VBM) to look for GM volume differences between the groups. Group comparison showed that GD patients with higher depressive symptoms exhibited significant GM volume increase in the left amygdala (p < 0.05, ROI FWE corrected). Amygdala GM volume positively correlated with depression scores. The authors extend previous findings in the field acknowledging the need for subgroup formation and comparisons in GD. Brain structural alterations in GD patients with depressive symptomatology might also exist. Depression co-morbidity in GD is an interesting field for future research with implications for therapy (i.e. personalized treatment) and the development of psychological or pharmacological interventions in GD patients with and without depression co-morbidity targeting amygdala and neighbouring regions.
Gesehen am 21.04.2020